KEEFEKTIFAN KEGIATAN KOLABORATIF MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PADA SKEMA MENGAJAR DI SATUAN PENDIDIKAN - Rochimah, Estuti; Refranisa, Refranisa; Lie, Titieandy; Ridzqo, Intan Findanavy; Demami, Aliviana; Puspita, Mutiara Eka (Jurnal Penelitian Kebijakan Pendidikan, 2022)
The effectiveness of school-university collaboration through the teaching assistance scheme as part of the Emancipated Learning Emancipated Campus (Merdeka Belajar Kampus Merdeka - MBKM) program. This research aims to analyze factors that influence the effectiveness of the MBKM program through the teaching assistant schemes in schools. The research was conducted using multiple linear regression method with SPSS as the tool. The independent variables were students’ interest and learning facilities, and the dependent variable was effectiveness. The result of the f test showed that students’ interest and learning facilities jointly affect 60.4% of the effectiveness of the MBKM implementation. Based on the results of the t test, interest had an influence of 40.221% on the effectiveness of MBKM implementation and learning facilities had an influence of 20.2176% on the effectiveness of MBKM implementation. From the results, it can be concluded that the teaching assistant scheme in schools had an influence of 60.4%, consisting of 40.2% students’ interest in SMKN 4 of South Tangerang towards MBKM activities and 20.2% learning facilities provided by mentors as teachers.